Optimizing the Use of Smart Contract to Protect Moral Rights of Songwriters on Over-The-Top Platform in Indonesia - Jennifer Angelique Loedijanto; Tasya Safiranita Ramli (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The rapid development of technology and information has created new dynamics in the creative music economy. The emergence of over-the-top (OTT) platforms as global distribution channels has increased accessibility, but also raised significant challenges regarding copyright protection, particularly the moral rights of songwriters. These issues are exacerbated by the widespread use of digital content without proper attribution and the unauthorized modification of original works. In this context, blockchain technology offers an innovative solution by providing transparency, security, and automation through smart contracts. This study employs a normative juridical method, analyzing primary legal sources such as Law No. 28 of 2014 on Copyright, along with secondary sources including journals and relevant literature. The findings indicate that smart contracts can enhance the protection of moral rights, especially attribution and integrity rights, by automatically embedding the creator’s identity and restricting unauthorized alterations. However, their implementation in Indonesia faces regulatory challenges due to the absence of specific legal provisions governing digital copyright protection. Therefore, Indonesia may adopt a framework similar to the Digital Millennium Copyright Act (DMCA), particularly its anti-circumvention provisions. Furthermore, effective implementation requires collaboration between the government, songwriters, and OTT platforms to ensure legal and practical enforcement.